A method for preparing phase change temperature-controlled lyocell fibers

CN122039244BActive Publication Date: 2026-10-23DEZHOU UNIV +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202610182840.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-02-09
Publication Date
2026-10-23
Estimated Expiration
2046-02-09

AI Technical Summary

Technical Problem

但NMMO在高温、酸性、金属离子存在等条件下极易发生分解,且Lyocell纤维生产加工温度远高于粘胶纤维,引入的任何添加剂都容易污染NMMO溶剂体系,甚至造成NMMO分解,一定程度上限制了功能性Lyocell纤维开发

Benefits of technology

1、采用本发明的制备方法制得的相变温控Lyocell纤维纤度为1.33~3.33dtex;干断裂强度为2.8~3.7cN/dtex,湿断裂强度为1.9~2.3cN/dtex;熔融相变焓值≥20J/g,50次水洗前后焓值变化≤1%(参照标准GB/T 19466.3-2004)。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122039244B_ABST
    Figure CN122039244B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of functional fibers, and in particular relates to a preparation method of phase change temperature control Lyocell fibers, which comprises preparation of phase change temperature control microparticle dispersion, modification of cellulose solution, mixing and fiber spinning. The present application forms a continuous film on the surface of aerogel phase change materials through acrylamide-cysteine Michael addition products, adds a small amount of glutaraldehyde, and performs micro-crosslinking of part of the amino groups in the acrylamide-cysteine Michael addition products to strengthen the film structure, so as to coat the aerogel phase change materials, and the remaining amino groups are prepared for subsequent grafting. A small amount of chloropropyl is modified on the cellulose macromolecule, the remaining amino groups on the surface of the phase change temperature control microparticles are subjected to nucleophilic substitution reaction with the modified chloropropyl on the cellulose in the modified cellulose solution to form C-N bonds, the binding force between the molecular chains is enhanced, and the binding force between the phase change materials and the cellulose macromolecule is also improved, so that the water washing resistance is better.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functional fiber technology, specifically relating to a method for preparing phase change temperature-controlled Lyocell fibers. Background Technology

[0002] The rapid development of science and technology has created conditions for the research and development of various high-tech textile raw materials in the textile industry. With the improvement of people's living standards, the application of differentiated and functional textiles has permeated all sectors of the national economy. Fiber materials with temperature control functions are favored by consumers in line with the green, low-carbon, and environmentally friendly consumption concept. Phase change energy storage temperature-regulating fibers utilize the heat absorption and release during the phase change process of the phase change material inside the fiber to achieve bidirectional automatic temperature regulation. It is a new type of intelligent temperature-regulating textile material that can spontaneously absorb and release heat within a certain range according to the ambient temperature. Phase change temperature-regulating fibers were first developed by NASA for the lunar landing program and were initially used in astronaut clothing and to protect precision experimental instruments in space. The emergence of phase change energy storage fibers has for the first time shifted humanity's traditional passive defense and warmth preservation methods to an active phase change temperature control method. It has a buffering and regulating effect on temperature changes, creating a favorable microclimate between the body and clothing, and has a climate regulation function. The most important aspect of temperature-controlled textiles is that they do not consume other energy sources, thus meeting the requirements of the current "dual-carbon" development. The technology of heat storage and temperature regulation textiles was selected by Newsday in the United States as one of the 21 innovations that will change human life in the 21st century.

[0003] Domestic and international companies have long used the viscose process to research and produce phase change energy storage viscose fibers. However, due to the low mechanical properties of viscose fibers and the limited amount of phase change microcapsule components added during production, the energy storage value of the prepared fibers is generally below 20 J / g, and the temperature control capability is insufficient to meet the requirements of high-end applications. The breakthrough in Lyocell fiber production technology using NMMO as a solvent provides a new approach for developing high-addition, high-enthalpy phase change energy storage regenerated cellulose fibers. As a novel type of cellulose fiber, Lyocell fiber has a green and environmentally friendly production process, and its mechanical properties are significantly improved compared to traditional cellulose fibers, gradually becoming a mainstream fiber in our daily lives. However, NMMO is highly susceptible to decomposition under conditions of high temperature, acidity, and the presence of metal ions. Furthermore, the processing temperature for Lyocell fiber production is much higher than that for viscose fiber, and any additives introduced can easily contaminate the NMMO solvent system, even causing NMMO decomposition, which to some extent limits the development of functional Lyocell fibers. CN117904735A discloses a method of dispersing phase change microcapsules in an NMMO aqueous solution, then dissolving cellulose in the phase change microcapsule dispersion to form a phase change microcapsule / cellulose solution. This solution is then filtered, degassed, and spun using a dry-jet wet spinning method to obtain phase change temperature-regulating Lyocell fibers. However, this method presents a risk of increased organic shell microcapsule particle size and breakage under high temperature and negative pressure conditions. CN115975605A discloses a method of using modified montmorillonite as a carrier to impregnate, adsorb, and encapsulate paraffin-based, fatty acid-based, and alcohol-based polymers to prepare composite phase change energy storage materials. This method presents a risk of phase change material leakage during subsequent applications.

[0004] Aerogels possess excellent structural properties, making them suitable as carriers for the adsorption, control, and regulation of reagents and drugs. SiO2 aerogels exhibit a porosity exceeding 80%, and their three-dimensional network structure results in a specific surface area of ​​800-1000 m². 2With a pore size of approximately 15 nm, silica aerogel micropowder exhibits great potential in the adsorption field, capable of efficiently adsorbing a variety of substances. Patent CN202411262371.7 discloses the preparation of phase change materials by vacuum adsorption of octadecane, a liquid phase change material, from silica aerogel micropowder. CN202411069874.2 discloses the addition of 3-aminopropyltriethoxysilane and deionized water to a mixed solution of terephthalaldehyde, octadecyl alcohol, and anhydrous ethanol, followed by stirring, high-pressure reactor reaction, and drying to obtain octadecyl alcohol / silica aerogel phase change material. CN202410506374.4 discloses a method for preparing modified silica-encapsulated paraffin phase change nanocapsules. CN201710740613.2 discloses the use of trimethylmethoxysilane as a novel precursor to prepare flexible silica aerogel, followed by the selection of a suitable phase change core material and a vacuum impregnation method to obtain a silica aerogel-based phase change composite material. The inventions described above confirm that silica aerogel can be used as a carrier for phase change materials and applied to the preparation of related materials, but do not address the issue of melting and loss of phase change materials at high temperatures.

[0005] The hydroxyl groups on the cellulose molecular chains of Lyocell fibers absorb water, causing the fibers to swell dramatically. This disrupts the hydrogen bonds between the molecular chains, weakens the lateral binding force, and increases the spacing between the megafibrillary structures within the fiber. This weakened structure splits along the fiber axis, forming nanofibrils. Lyocell fibers have a high proportion of amorphous regions, and the loose molecular chains in these regions are easily damaged by external forces. This means that in a wet state, the molecular chains are prone to slippage, leading to microfibril separation. Simultaneously, during the spinning process, the core layer solvent evaporates slowly, resulting in a more porous core layer structure that struggles to constrain the microfibrils in the sheath. Therefore, fibrillation of Lyocell fibers is quite severe. To meet the phase change temperature control function of the fibers, a large amount of silica aerogel-loaded phase change material is added to the spinning solution. However, the addition of a large amount of silica aerogel hinders the orderly arrangement of cellulose molecular chains, further reducing the mechanical strength of the fibers and exacerbating fibrillation. Summary of the Invention

[0006] To address the problems existing in the prior art, this invention provides a method for preparing phase change temperature-controlled Lyocell fibers. Silica aerogel nanospheres are used as a framework to adsorb phase change materials, which are then dispersed and coated to prepare phase change microparticle materials with a core-shell structure. This prevents damage and leakage of phase change materials caused by pressure and temperature changes during subsequent fiber preparation and application, stabilizing product quality and temperature control function. Simultaneously, it increases the number of wet abrasion cycles of the fiber and improves the fibrillation problem of Lyocell fibers.

[0007] A method for preparing phase change temperature-controlled Lyocell fibers, the method comprising the following steps: S1. Preparation of phase change temperature-controlled microparticle dispersion S11. Heat the phase change material to melt at 60-70℃; add the silica aerogel that has been pulverized to below 1μm and dried into the reaction vessel, heat at 60-70℃, stir, and vacuum, then add the molten phase change material, vacuum impregnate for 2-3 hours, and after impregnation, cool at 10-15℃ for 40-60 minutes to obtain the aerogel phase change material. S12. Acrylamide, cysteine, triethylamine, and deionized water are added to the reactor in proportion. The pH is adjusted to 8-9 with NaOH solution. The material temperature in the reactor is controlled at 30-40℃. The reaction is stirred for 3-4 hours. The carbon-carbon double bond of acrylamide and the thiol group of cysteine ​​undergo Michael addition reaction to form a thioether bond. The pH is then adjusted to neutral with hydrochloric acid solution to obtain the shell material solution. S13. Add aerogel phase change material, polyvinylpyrrolidone, and deionized water to a homogenizer, control the rotation speed at 3500-4000 r / min, and homogenize at 20-25℃ for 10-15 min. Then add shell material solution and glutaraldehyde and stir at low speed for 50-60 min to obtain a phase change temperature-controlled microparticle dispersion with core-shell structure and D90≤2.0μm.

[0008] The amino, carboxyl, and amide groups in the acrylamide-cysteine ​​Michael addition product form hydrogen bonds with the silanol groups on the surface of the aerogel phase change material, forming a continuous film on the surface of the aerogel phase change material. With the addition of a small amount of glutaraldehyde, some of the amino groups in the acrylamide-cysteine ​​Michael addition product undergo micro-crosslinking to strengthen the film structure, thereby encapsulating the aerogel phase change material. The remaining amino groups are prepared for subsequent grafting.

[0009] Preferably, the phase change material in S11 is a mixture of n-octadecane and 48# paraffin, with a mass ratio of 9 to 9.5:1.

[0010] Preferably, the mass ratio of silica aerogel to phase change material in S11 is 1:1.5 to 2.

[0011] Preferably, the stirring speed of S11 is 200-300 r / min, and the vacuum degree is ≤-0.08 MPa.

[0012] Preferably, the amount of acrylamide added in S12 is 15-20% of the mass of the aerogel phase change material.

[0013] Preferably, the mass ratio of acrylamide to deionized water in S12 is 1:6 to 8.

[0014] Preferably, the molar ratio of cysteine, acrylamide, and triethylamine in S12 is 1:1 to 1.2:0.2 to 0.4.

[0015] Preferably, the mass ratio of aerogel phase change material, polyvinylpyrrolidone and deionized water in S13 is 10-12:0.1-0.2:70-80.

[0016] Preferably, the amount of glutaraldehyde added in S13 is 1 to 2% of the mass of cysteine ​​in S12.

[0017] Preferably, the low-speed stirring rate in S13 is 100-200 r / min.

[0018] S2. Pretreatment of pulp Add the crushed pulp to water to swell for 40-50 minutes, then slowly add 3-chloropropylmethyldimethoxysilane and keep it at 30-40℃ for 1-2 hours to modify a small amount of chloropropyl groups on the cellulose macromolecules. Remove and drain for later use.

[0019] Preferably, the pulp is one or more of wood pulp and cotton pulp, with a degree of polymerization of 500 to 800.

[0020] Preferably, the ratio of pulp to water is 1:4 to 5.

[0021] Preferably, the amount of 3-chloropropylmethyldimethoxysilane added is 4-6% of the pulp mass, and the addition rate is 2-4 ml / min.

[0022] S3. Preparation of phase change temperature-controlled microparticle-cellulose mixed solution The phase change temperature-controlled microparticle dispersion was added to a 50% NMMO solution and stirred for 10–20 min. Then, pretreated pulp was added, and the temperature was raised to 90–110 °C. Under a vacuum of ≤-0.08 MPa, the microparticles were dehydrated and degassed to dissolve them. The remaining amino groups on the surface of the phase change temperature-controlled microparticles underwent nucleophilic substitution reactions with the chloropropyl groups modified on the cellulose, thereby grafting the phase change temperature-controlled microparticles onto the cellulose macromolecules to obtain a phase change temperature-controlled microparticle-cellulose mixed solution.

[0023] Preferably, the amount of pretreated pulp added is 3 to 5% of the mass of 50% NMMO solution.

[0024] Preferably, the amount of the phase change temperature-controlled microparticle dispersion added is calculated as 25% to 35% of the mass of cellulose in the phase change temperature-controlled microparticle-cellulose mixed solution.

[0025] Grafting not only strengthens the bond between the phase change material and the cellulose macromolecules, resulting in a more uniform distribution, but also enhances the inter-chain bonding force through the nucleophilic substitution reaction between the remaining amino groups on the surface of the phase change temperature-controlled microparticles and the chloropropyl groups modified on the cellulose in the modified cellulose solution, forming CN bonds. Simultaneously, the thioether bonds on the surface of the phase change temperature-controlled microparticles exhibit better flexibility, mitigating surface chain delamination caused by stress concentration under external forces such as wet friction. Through the synergistic effect of these multiple mechanisms, fibrillation of Lyocell fibers is suppressed.

[0026] S4, fiber spinning The phase change temperature-controlled microparticle-cellulose mixture solution is filtered and spun using a dry-jet wet spinning process. The filaments ejected from the spinneret first pass through an air gap section, are cooled by a blower system, and then immersed in a spinning coagulation bath at a temperature of 15-25°C. After being drawn 2-4 times, the fibers are washed, oiled, and dried to obtain phase change temperature-controlled Lyocell fibers with different fineness.

[0027] Preferably, the air gap section has a length of 6-8 cm, the spinning rate is 35-50 m / min, and the coagulation bath is a 10-14% NMMO solution.

[0028] Preferably, the water used for washing is softened water at a temperature of 60–80°C; Preferably, the concentration of the oil bath used for oiling is 4-6 g / L, and the temperature is 50-60°C.

[0029] Due to the adoption of the above technical solution, the beneficial effects of the present invention are as follows: 1. The phase change temperature-controlled Lyocell fiber prepared by the method of the present invention has a fineness of 1.33 to 3.33 dtex; a dry breaking strength of 2.8 to 3.7 cN / dtex; a wet breaking strength of 1.9 to 2.3 cN / dtex; a melt phase change enthalpy ≥ 20 J / g; and an enthalpy change ≤ 1% before and after 50 water washes (refer to standard GB / T 19466.3-2004).

[0030] 2. By forming a coating film on the aerogel phase change material, this invention further reduces the risk of damage and leakage of the phase change material caused by pressure and temperature changes during the subsequent fiber preparation process. The loss rate of the phase change material during fiber preparation is less than 1.0%.

[0031] 3. The phase change temperature control Lyocell fiber prepared by this invention has a lighter degree of fibrillation and a wet abrasion cycle of ≥100 times (standard FZ / T52019—2018), making it more practical and more spinnable. Attached Figure Description

[0032] Figure 1 This is a TEM image of the longitudinal section of the fiber in Example 1; Figure 2 This is a TEM image of the fiber cross-section in Example 1. Detailed Implementation

[0033] To further illustrate the technical means and effects of the present invention in achieving the intended purpose, the following detailed description of the specific implementation methods, structures, features and effects of the present invention, in conjunction with preferred embodiments, is provided below.

[0034] Example 1: A method for preparing phase change temperature-controlled Lyocell fibers, the method comprising the following steps: S1. Preparation of phase change temperature-controlled microparticle dispersion S11. Heat the phase change material to melt at 65°C; add the silica aerogel that has been pulverized to below 1μm and dried into the reactor, heat at 65°C, stir, and vacuum, then add the molten phase change material, vacuum impregnate for 3 hours, and cool at 12°C for 50 minutes after impregnation to obtain the aerogel phase change material. S12. Acrylamide, cysteine, triethylamine, and deionized water are added to the reactor in proportion. The pH is adjusted to 8.5 with 1 mol / L NaOH solution. The material temperature in the reactor is controlled at 35℃. The reaction is stirred for 3.5 h. The carbon-carbon double bond of acrylamide and the thiol group of cysteine ​​undergo Michael addition reaction to form a thioether bond. The pH is then adjusted to neutral with 1 mol / L hydrochloric acid solution to obtain the shell material solution. S13. Add aerogel phase change material, polyvinylpyrrolidone, and deionized water to a homogenizer, control the rotation speed at 3500 r / min, homogenize at 23℃ for 15 min, then add shell material solution and glutaraldehyde and stir at low speed for 55 min to obtain a phase change temperature-controlled microparticle dispersion with core-shell structure and D90≤2.0μm.

[0035] The phase change material in S11 is a mixture of n-octadecane and 48# paraffin wax in a mass ratio of 9.4:1.

[0036] The mass ratio of silica aerogel to phase change material in S11 is 1:1.7.

[0037] The S11 stirring speed is 250 r / min, and the vacuum degree is -0.08 MPa.

[0038] The amount of acrylamide added in S12 is 18% of the mass of the aerogel phase change material.

[0039] The mass ratio of acrylamide to deionized water in S12 is 1:7.

[0040] The molar ratio of cysteine, acrylamide, and triethylamine in S12 is 1:1.1:0.3.

[0041] The mass ratio of aerogel phase change material, polyvinylpyrrolidone, and deionized water in S13 is 11:0.15:75.

[0042] The amount of glutaraldehyde added in S13 is 1.5% of the mass of cysteine ​​in S12.

[0043] The stirring speed in S13 is 150 r / min.

[0044] S2. Pretreatment of pulp The pulverized wood pulp with a degree of polymerization of 700 was added to water and swelled for 50 minutes. Then, 3-chloropropylmethyldimethoxysilane was slowly added and the mixture was kept at 35°C for 2 hours to modify a small amount of chloropropyl groups on the cellulose macromolecules. The pulp was then drained and set aside for later use.

[0045] The ratio of wood pulp to water is 1:4.

[0046] The amount of 3-chloropropylmethyldimethoxysilane added is 5% of the wood pulp mass, and the addition rate is 3 ml / min.

[0047] S3. Preparation of phase change temperature-controlled microparticle-cellulose mixed solution The phase change temperature-controlled microparticle dispersion was added to a 50% NMMO solution and stirred for 10–20 min. Then, pretreated pulp was added, and the mixture was heated to 100 °C under a vacuum of -0.08 MPa to dehydrate and degas the microparticles until they dissolved. The remaining amino groups on the surface of the phase change temperature-controlled microparticles underwent a nucleophilic substitution reaction with the chloropropyl groups modified on the cellulose, thereby grafting the phase change temperature-controlled microparticles onto the cellulose macromolecules to obtain a phase change temperature-controlled microparticle-cellulose mixed solution.

[0048] The amount of the pretreated pulp added is 4% of the mass of 50% NMMO solution.

[0049] The amount of phase change temperature-controlled microparticle dispersion added is calculated as 30% of the mass of cellulose in the phase change temperature-controlled microparticle-cellulose mixed solution.

[0050] S4, fiber spinning The phase change temperature-controlled microparticle-cellulose mixture solution is filtered and spun using a dry-jet wet spinning process. The filaments ejected from the spinneret first pass through an air gap section, are cooled by a blower system, and then immersed in a spinning coagulation bath at a temperature of 20°C. After being stretched three times, the fibers are washed, oiled, and dried to obtain phase change temperature-controlled Lyocell fibers.

[0051] The air gap section is 7 cm long, the spinning rate is 40 m / min, and the coagulation bath is a 12% NMMO solution.

[0052] The washing process uses softened water at a temperature of 70°C. The oil bath concentration for oiling is 5 g / L, and the temperature is 55°C.

[0053] Example 2: A method for preparing phase change temperature-controlled Lyocell fibers, the method comprising the following steps: S1. Preparation of phase change temperature-controlled microparticle dispersion S11. Heat the phase change material to melt at 60°C; add the silica aerogel that has been pulverized to below 1μm and dried into the reactor, heat at 60°C, stir, and vacuum, then add the molten phase change material, vacuum impregnate for 2 hours, and cool at 10°C for 40 minutes after impregnation to obtain the aerogel phase change material. S12. Acrylamide, cysteine, triethylamine, and deionized water are added to the reactor in proportion. The pH is adjusted to 8 with 1 mol / L NaOH solution. The material temperature in the reactor is controlled at 30℃. The reaction is stirred for 3 hours. The carbon-carbon double bond of acrylamide and the thiol group of cysteine ​​undergo Michael addition reaction to form a thioether bond. The pH is then adjusted to neutral with 1 mol / L hydrochloric acid solution to obtain the shell material solution. S13. Add aerogel phase change material, polyvinylpyrrolidone, and deionized water to a homogenizer, control the rotation speed at 4000 r / min, homogenize at 20℃ for 10 min, then add shell material solution and glutaraldehyde and stir at low speed for 50 min to obtain a phase change temperature-controlled microparticle dispersion with core-shell structure and D90≤2.0μm.

[0054] The phase change material in S11 is a mixture of n-octadecane and 48# paraffin wax in a mass ratio of 9:1.

[0055] The mass ratio of silica aerogel to phase change material in S11 is 1:1.5.

[0056] The stirring speed of S11 is 200 r / min, and the vacuum degree is -0.08 MPa.

[0057] The amount of acrylamide added in S12 is 15% of the mass of the aerogel phase change material.

[0058] The mass ratio of acrylamide to deionized water in S12 is 1:6.

[0059] The molar ratio of cysteine, acrylamide, and triethylamine in S12 is 1:1:0.2.

[0060] The mass ratio of aerogel phase change material, polyvinylpyrrolidone, and deionized water in S13 is 10:0.1:70.

[0061] The amount of glutaraldehyde added in S13 is 1% of the mass of cysteine ​​in S12.

[0062] The stirring speed in S13 is 100 r / min.

[0063] S2. Pretreatment of pulp The pulverized wood pulp with a degree of polymerization of 500 was added to water and swelled for 40 minutes. Then, 3-chloropropylmethyldimethoxysilane was slowly added and the mixture was kept at 30°C for 1 hour to modify a small amount of chloropropyl groups on the cellulose macromolecules. The pulp was then drained and set aside for later use.

[0064] The ratio of wood pulp to water is 1:4.

[0065] The amount of 3-chloropropylmethyldimethoxysilane added is 4% of the wood pulp mass, and the addition rate is 2 ml / min.

[0066] S3. Preparation of phase change temperature-controlled microparticle-cellulose mixed solution The phase change temperature-controlled microparticle dispersion was added to a 50% NMMO solution and stirred for 10 min. Then, pretreated pulp was added, and the temperature was raised to 90℃. The vacuum degree was -0.08 MPa to dehydrate and defoam the microparticles until they dissolved. The remaining amino groups on the surface of the phase change temperature-controlled microparticles reacted with the chloropropyl groups modified on the cellulose to nucleophilically replace them, thereby grafting the phase change temperature-controlled microparticles onto the cellulose macromolecules to obtain a phase change temperature-controlled microparticle-cellulose mixed solution.

[0067] The amount of the pretreated pulp added is 3% of the mass of 50% NMMO solution.

[0068] The amount of phase change temperature-controlled microparticle dispersion added is calculated as 25% of the mass of cellulose in the phase change temperature-controlled microparticle-cellulose mixed solution.

[0069] S4, fiber spinning The phase change temperature-controlled microparticle-cellulose mixture solution is filtered and spun using a dry-jet wet spinning process. The filaments ejected from the spinneret first pass through an air gap section, are cooled by a blower system, and then immersed in a spinning coagulation bath at a temperature of 15°C. After being stretched four times, the fibers are washed, oiled, and dried to obtain phase change temperature-controlled Lyocell fibers.

[0070] The air gap section is 6 cm long, the spinning rate is 50 m / min, and the coagulation bath is a 10% NMMO solution.

[0071] The washing process uses softened water at a temperature of 60°C. The oil bath concentration for oiling is 4 g / L, and the temperature is 50°C.

[0072] Example 3: A method for preparing phase change temperature-controlled Lyocell fibers, the method comprising the following steps: S1. Preparation of phase change temperature-controlled microparticle dispersion S11. Heat the phase change material to melt at 70°C; add the silica aerogel that has been pulverized to below 1μm and dried into the reactor, heat at 70°C, stir, and vacuum, then add the molten phase change material, vacuum impregnate for 2.5 hours, and cool at 15°C for 60 minutes after impregnation to obtain the aerogel phase change material. S12. Acrylamide, cysteine, triethylamine, and deionized water are added to the reactor in proportion. The pH is adjusted to 9 with 1 mol / L NaOH solution. The material temperature in the reactor is controlled at 40℃. The reaction is stirred for 4 hours. The carbon-carbon double bond of acrylamide and the thiol group of cysteine ​​undergo Michael addition reaction to form a thioether bond. The pH is then adjusted to neutral with 1 mol / L hydrochloric acid solution to obtain the shell material solution. S13. Add aerogel phase change material, polyvinylpyrrolidone, and deionized water to a homogenizer, control the rotation speed at 3700 r / min, homogenize at 25℃ for 15 min, then add shell material solution and glutaraldehyde and stir at low speed for 60 min to obtain a phase change temperature-controlled microparticle dispersion with core-shell structure and D90≤2.0μm.

[0073] The phase change material in S11 is a mixture of n-octadecane and 48# paraffin wax in a mass ratio of 9.5:1.

[0074] The mass ratio of silica aerogel to phase change material in S11 is 1:2.

[0075] The stirring speed of S11 is 300 r / min, and the vacuum degree is -0.08 MPa.

[0076] The amount of acrylamide added in S12 is 20% of the mass of the aerogel phase change material.

[0077] The mass ratio of acrylamide to deionized water in S12 is 1:8.

[0078] The molar ratio of cysteine, acrylamide, and triethylamine in S12 is 1:1.2:0.4.

[0079] The mass ratio of aerogel phase change material, polyvinylpyrrolidone, and deionized water in S13 is 12:0.2:80.

[0080] The amount of glutaraldehyde added in S13 is 2% of the mass of cysteine ​​in S12.

[0081] The stirring speed in S13 is 200 r / min.

[0082] S2. Pretreatment of pulp The pulverized wood pulp with a degree of polymerization of 800 was added to water and swelled for 45 minutes. Then, 3-chloropropylmethyldimethoxysilane was slowly added and the mixture was kept at 40°C for 1.5 hours to modify a small amount of chloropropyl groups on the cellulose macromolecules. The pulp was then drained and set aside for later use.

[0083] The ratio of wood pulp to water is 1:5.

[0084] The amount of 3-chloropropylmethyldimethoxysilane added is 6% of the wood pulp mass, and the addition rate is 4 ml / min.

[0085] S3. Preparation of phase change temperature-controlled microparticle-cellulose mixed solution The phase change temperature-controlled microparticle dispersion was added to a 50% NMMO solution and stirred for 20 min. Then, pretreated pulp was added, and the temperature was raised to 110℃ with a vacuum of -0.08 MPa. The microparticles were dehydrated and degassed to dissolve them. The remaining amino groups on the surface of the phase change temperature-controlled microparticles underwent nucleophilic substitution reactions with the chloropropyl groups modified on the cellulose, thereby grafting the phase change temperature-controlled microparticles onto the cellulose macromolecules to obtain a phase change temperature-controlled microparticle-cellulose mixed solution.

[0086] The amount of the pretreated pulp added is 5% of the mass of 50% NMMO solution.

[0087] The amount of phase change temperature-controlled microparticle dispersion added is calculated as 35% of the mass of cellulose in the phase change temperature-controlled microparticle-cellulose mixed solution.

[0088] S4, fiber spinning The phase change temperature-controlled microparticle-cellulose mixture solution is filtered and spun using a dry-jet wet spinning process. The filaments ejected from the spinneret first pass through an air gap section, are cooled by a blower system, and then immersed in a spinning coagulation bath at a temperature of 25°C. After being stretched twice, the fibers are washed, oiled, and dried to obtain phase change temperature-controlled Lyocell fibers.

[0089] The air gap section is 8 cm long, the spinning rate is 35 m / min, and the coagulation bath is a 14% NMMO solution.

[0090] The washing process uses softened water at a temperature of 80°C. The oil bath concentration for oiling is 6 g / L, and the temperature is 60°C.

[0091] Comparative Example 1: A representative example, Example 1, was selected, in which the amount of glutaraldehyde added in S13 was increased to 5% of the mass of cysteine ​​in S12, while the rest remained the same as in Example 1.

[0092] Comparative Example 2: A representative example, Example 1, was selected, in which glutaraldehyde was not added to S13, and all other steps were the same as in Example 1. This was used as Comparative Example 2.

[0093] Comparative Example 3: A representative example, Example 1, was selected. The modified cellulose solution in S2 was removed, and the unmodified cellulose solution was used directly in S3. All other steps were the same as in Example 1. This was used as Comparative Example 3.

[0094] Comparative Example 4: A representative example, Example 1, was selected. Steps S12 and S13 were omitted. The aerogel phase change material obtained in S11, polyvinylpyrrolidone, and deionized water were directly added to a homogenizer. The rotation speed was controlled at 2000 r / min, and the homogenization was carried out at 15°C for 15 min to obtain an aerogel phase change material dispersion with D90≤2.0μm. All other steps were the same as in Example 1, and this was used as Comparative Example 4.

[0095] The fibers prepared in the examples and comparative examples were subjected to performance testing, as detailed in the table below.

[0096] As can be seen from the table, the addition of glutaraldehyde in S13 of Comparative Example 1 is relatively large, which leads to a denser coating film on the surface of the aerogel phase change material. At the same time, the reduction of surface amino groups leads to a reduction in subsequent grafting between the aerogel and cellulose macromolecules and a weakening of intermolecular binding forces. Therefore, Comparative Example 1 has a lower loss rate of phase change material in fiber preparation, a higher fiber enthalpy value, but a lower strength, an increased water washing loss rate, a lower number of wet abrasion cycles of the fiber compared to Example 1, and more severe fibrillation.

[0097] In Comparative Example 2, glutaraldehyde was not added in S13, resulting in insufficient strength of the coating film on the surface of the aerogel phase change material. It was easily detached after pressure and temperature changes during spinning, leading to melting and loss of the phase change material. After the surface film was detached, some of the aerogel phase change material agglomerated or could not be grafted onto the cellulose macromolecules, causing a certain degree of decrease in fiber strength and washability. The number of wet abrasion cycles of the fiber was low, but most of the coating film on the surface of the aerogel phase change material did not detach. It could react with the cellulose macromolecules to compensate for some of the defects caused by agglomeration. Therefore, although it was lower than Example 1, it was better than Comparative Example 4.

[0098] Comparative Example 3 removed the modified cellulose solution in S2 and directly used the unmodified cellulose solution in S3. Therefore, although the phase change temperature-controlled microparticles were evenly distributed in the fiber, they could not be grafted onto the cellulose macromolecules. The hydrogen bonding forces generated between them and the cellulose macromolecules were weak. As a result, the mechanical properties of Comparative Example 3 were lower than those of Example 1, the number of wet abrasion cycles of the fiber was low, and the enthalpy value of subsequent water washing decreased significantly.

[0099] In Comparative Example 4, the aerogel phase change material was directly prepared into a dispersion and added to the modified cellulose solution. The loss rate of the phase change material during fiber preparation was high, and the subsequent water washing enthalpy value decreased significantly. At the same time, the large amount of aerogel phase change material further hindered the orderly arrangement between cellulose macromolecules, resulting in a decrease in fiber mechanical properties and a low number of wet abrasion cycles, and an aggravation of fibrillation.

[0100] In summary, this invention, by forming a coating film on the aerogel phase change material, further reduces the risk of damage and leakage of the phase change material due to pressure and temperature changes during subsequent fiber preparation. Simultaneously, the CN bonds formed by the nucleophilic substitution reaction between the remaining amino groups on the surface of the phase change temperature-controlled microparticles and the chloropropyl groups modified on the cellulose in the modified cellulose solution enhance the binding force between molecular chains and also strengthen the binding force between the phase change temperature-controlled microparticles and the cellulose macromolecules. Furthermore, the thioether bonds on the surface of the phase change temperature-controlled microparticles exhibit better flexibility, mitigating the surface molecular chain peeling caused by stress concentration under external forces such as wet friction. Through the synergistic effect of these multiple mechanisms, fibrillation of Lyocell fibers is inhibited, as evidenced by the number of wet abrasion cycles.

[0101] Unless otherwise specified, all proportions and percentages mentioned in this invention are mass proportions and mass percentages; all raw materials are commercially available.

[0102] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A method for preparing phase change temperature-controlled Lyocell fibers, characterized in that, The preparation method includes the preparation of phase change temperature-controlled microparticle dispersion, pretreatment of pulp, preparation of phase change temperature-controlled microparticle-cellulose mixed solution, and fiber spinning. The phase change temperature-controlled microparticle dispersion is prepared as follows: S11. Heat the phase change material to melt at 60-70℃; add the silica aerogel that has been pulverized to below 1μm and dried into the reaction vessel, heat at 60-70℃, stir, and vacuum, then add the molten phase change material, vacuum impregnate for 2-3 hours, and after impregnation, cool at 10-15℃ for 40-60 minutes to obtain the aerogel phase change material. S12. Add acrylamide, cysteine, triethylamine, and deionized water to the reactor in proportion, adjust the pH to 8-9 with NaOH solution, control the material temperature in the reactor to 30-40℃, stir the reaction for 3-4 hours, and then adjust the pH to neutral with hydrochloric acid solution to obtain the shell material solution. S13. Add aerogel phase change material, polyvinylpyrrolidone, and deionized water to a homogenizer, control the rotation speed at 3500-4000 r / min, homogenize at 20-25℃ for 10-15 min, then add shell material solution and glutaraldehyde and stir at low speed for 50-60 min to obtain a phase change temperature-controlled microparticle dispersion with core-shell structure and D90≤2.0μm. The amount of glutaraldehyde added in S13 is 1-2% of the mass of cysteine ​​in S12; The pretreatment of the pulp is as follows: the pulverized pulp is added to water to swell for 40-50 minutes, then 3-chloropropylmethyldimethoxysilane is slowly added, and the pulp is kept at 30-40°C for 1-2 hours. The pulp is then drained and set aside for later use. The phase change temperature-controlled microparticle-cellulose mixed solution is prepared by adding the phase change temperature-controlled microparticle dispersion to a 50% NMMO solution and stirring for 10-20 minutes, then adding the pretreated pulp, heating to 90-110℃, vacuum degree ≤-0.08MPa, dehydrating and defoaming to dissolve it, and obtaining the phase change temperature-controlled microparticle-cellulose mixed solution.

2. The method for preparing phase change temperature-controlled Lyocell fiber according to claim 1, characterized in that, The phase change material in S11 is a mixture of n-octadecane and 48# paraffin, with a mass ratio of 9 to 9.5:

1. The mass ratio of silica aerogel to phase change material in S11 is 1:1.5 to 2; The stirring speed of S11 is 200-300 r / min, and the vacuum degree is ≤-0.08 MPa.

3. The method for preparing phase change temperature-controlled Lyocell fiber according to claim 1, characterized in that, The amount of acrylamide added in S12 is 15-20% of the mass of the aerogel phase change material; The mass ratio of acrylamide to deionized water in S12 is 1:6-8; The molar ratio of cysteine, acrylamide, and triethylamine in S12 is 1:1 to 1.2:0.2 to 0.

4.

4. The method for preparing phase change temperature-controlled Lyocell fiber according to claim 1, characterized in that, The mass ratio of aerogel phase change material, polyvinylpyrrolidone, and deionized water in S13 is 10–12: 0.1–0.2: 70–80. The low-speed stirring rate in S13 is 100-200 r / min.

5. The method for preparing phase change temperature-controlled Lyocell fiber according to claim 1, characterized in that, The pulp is one or more of wood pulp and cotton pulp, with a degree of polymerization of 500 to 800. The ratio of pulp to water is 1:4 to 5; The amount of 3-chloropropylmethyldimethoxysilane added is 4-6% of the pulp mass, and the addition rate is 2-4 ml / min.

6. The method for preparing phase change temperature-controlled Lyocell fiber according to claim 1, characterized in that, The amount of the pretreated pulp added is 3-5% of the mass of a 50% NMMO solution; The amount of phase change temperature-controlled microparticle dispersion added is calculated as 25-35% of the mass of cellulose in the phase change temperature-controlled microparticle-cellulose mixed solution.

7. The method for preparing phase change temperature-controlled Lyocell fiber according to claim 1, characterized in that, The fiber spinning process involves filtering a phase change temperature-controlled microparticle-cellulose mixed solution and then spinning it using a dry-jet wet spinning process. The fiber bundles ejected from the spinneret first pass through an air gap section, are cooled by a blowing system, and then immersed in a spinning coagulation bath at a temperature of 15–25°C. After being drawn 2–4 times, the fibers are washed, oiled, and dried to obtain phase change temperature-controlled Lyocell fibers with different fineness.

8. The method for preparing phase change temperature-controlled Lyocell fiber according to claim 7, characterized in that, The air gap section is 6-8 cm long, the spinning rate is 35-50 m / min, and the coagulation bath is a 10-14% NMMO solution. The washing process uses softened water at a temperature of 60–80°C. The concentration of the oil bath used for oiling is 4-6 g / L, and the temperature is 50-60℃.

Citation Information

Patent Citations

  • A method for preparing a flexible silica aerogel-based phase change composite material

    CN107523275B

  • Preparation method of composite phase change energy storage material

    CN115975605A

  • Preparation method of modified silicon dioxide coated paraffin phase change nano microcapsule

    CN118480332A

  • Preparation method of octadecanol / silicon dioxide aerogel composite material

    CN118978896A

  • Preparation process of silicon dioxide aerogel integrated ball-milling and vacuum adsorption phase change material

    CN119098272A